X‐ray crystallography and NMR studies of domain‐swapped canecystatin‐1. (11th January 2013) - Valadares, Napoleão F.; de, Rodrigo; Cavini, Italo A.; de, Ivo; D'Muniz Pereira, Humberto; Soares‐Costa, Andrea; Henrique‐Silva, Flavio; Kalbitzer, Hans R.; Munte, Claudia E.; Garratt, Richard C.
<x xml:space="preserve">Abstract</x> The three‐dimensional structure of canecystatin‐1, a potent inhibitor of cysteine proteases from sugarcane (Saccharum officinarum), has been solved in two different crystal forms. In both cases, it is seen to exist as a domain‐swapped dimer, the first such observation for a cystatin of plant origin. Size exclusion chromatography and multidimensional NMR spectroscopy show the dimer to be the dominant species in solution, despite the presence of a measurable quantity of monomer undergoing slow exchange. The latter is believed to be the active species, whereas the domain‐swapped dimer is presumably inactive, as its first inhibitory loop has been extended to form part of a long β‐strand that forms a double‐helical coiled coil with its partner from the other monomer. A similar structure is observed in human cystatin C, but the spatial disposition of the two lobes of the dimer is rather different. Dimerization is presumably a mechanism by which canecystatin‐1 can be kept inactive within the plant, avoiding the inhibition of endogenous proteases. The structure described here provides a platform for the rational design of specific cysteine protease inhibitors for biotechnological applications. Database The coordinates and structure factors have been deposited in the Protein Data Bank under the accession codes 3UL5 and 3UL6. Structured digital abstract Canecystatin-1 and Canecystatin-1 bind by molecular sieving (View Interaction: 1, 2) Canecystatin-1 and Canecystatin-1 bind by nuclear magnetic resonance (View interaction) Canecystatin-1 and Canecystatin-1 bind by dynamic light scattering (View interaction) Canecystatin-1 and Canecystatin-1 bind by x-ray crystallography (View interaction)